PROFESSIONAL ETHICS AND INTEGRITY IN HUMAN RESOURCE MANAGEMENT PRACTICES IN INDONESIAN NATIONAL COMPANIES - Dewi, Irma Nurmala; Khaeruman, Khaeruman; Mat Noor, Noorsidi Aizuddin (Yayasan Education and Social Center, 2025)
The objective of this investigation is to evaluate the effectiveness of human resource management (HRM) strategies in enhancing organizational performance within Indonesian organizations. The methodology employed is qualitative research with a descriptive approach, which entails in-depth interviews and observations of human resource staff and managers. The results show that digital-based HRM, a transparent compensation system, and employee competency improvement through continuous training are essential factors in achieving organizational effectiveness. In addition to productivity, the implemented strategies aim to foster a collaborative work culture and an environment that promotes employee well-being. The findings of this study reinforce the results of previous studies that highlight the role of digital HRM in enhancing operational efficiency and informing strategic decision-making. This research aims to help organizations develop HRM policies that are responsive to shifts in the business landscape and technological advancements.